Family planning in Taranto - De Benedetto, Francesco (Medicina e Morale, 2024)
The aim of the investigation carried out in Taranto was to ascertain how birth control was understood and practised in one of the most densely populated centres in the Mezzogiorno, recently invested by a massive industrialisation process.